Indoor Air Quality in Laboratories and Its Relationship with Psychological Performance Among University Students in Malaysia - Nazman, Muhammad; Mohd Hatta, Puteri Balqis; Suhaimi, Nur Faseeha (Universitas Airlangga, 2024)
Introduction: Poor indoor air quality (IAQ) in work environments can reduce productivity and decrease overall performance. This study examines IAQ in university laboratories and its relationship with psychological performance among students in Malaysia. Methods: This cross-sectional study was conducted from October to November 2023 in six laboratories at a Malaysian university, categorised into chemical and non-chemical. A total of 117 students aged 18 to 40 participated. IAQ was measured in real-time for 8 hours during weekdays using instruments for particulate matter (PM2.5, PM10), carbon monoxide (CO), total volatile organic compounds (TVOC), airborne microorganisms, carbon dioxide (CO2), temperature in °C, relative humidity (RH), and air movement. Psychological performance was assessed using the General Health Questionnaire (GHQ-12) and Post Occupancy Evaluation (POE). Data analysis was performed using Kruskal-Wallis, One-Way ANOVA, and Chi-Square tests. Results and Discussion: Significant differences in IAQ parameters were observed for PM2.5 (p=0.007), PM10 (p=0.020), CO2 (p=0.024) and RH (p=0.043). Psychological distress affected 41.9% of students based on the predefined threshold. High CO levels (≥0.67 ppm) and elevated temperatures (≥23.28°C) were significantly associated with increased psychological distress (p=0.011). Students exposed to these conditions were 1.3 times more likely to experience distress (OR=1.3). Conclusion: Specific IAQ parameters, particularly CO and temperature, critically impact students’ psychological well-being. Improving IAQ by reducing CO levels and maintaining optimal temperatures may enhance mental health and performance. Improving IAQ by reducing CO levels and maintaining optimal temperatures may enhance mental health and performance. However, external factors such as personal stressors could not be entirely controlled.